Association between troponin and outcome in patients with chest pain and rapid atrial fibrillation: a retrospective study of a single-center 10-year cohort. (13th May 2022) - García, Ana; Miota, Natalia; Miró, Òscar; López-Ayala, Pedro; López-Barbeito, Beatriz; Strebel, Ivo; Xipell, Carolina; Fuenzalida, Carolina; Martínez-Nadal, Gemma; Boeddinghaus, Jasper; Nestelberger, Thomas; Twerenbold, Raphael; et al.
Abstract : Background and objective: The prognosis of myocardial infarction in patients with rapid atrial fibrillation (RAF) is poorly known. We sought to ascertain if troponin concentrations are associated with a higher risk of major adverse cardiovascular events (MACE) in patients with RAF and chest discomfort suggestive of coronary origin. Methods: We retrospectively reviewed all consecutive patients attending an emergency department of a single-center (2008–2017) with chest pain suggestive of coronary origin who had RAF and at least one troponin determination. Patients were classified as having normal/increased troponin. They were followed until December 2019 to detect MACE (primary outcome), which included acute coronary syndrome (ACS), revascularization, stroke, or all-cause death. In addition to cardiovascular death and type I myocardial infarction, these were considered secondary outcomes. The adjusted risk was determined by Cox regression, and sensitivity analysis were run. Relationship between troponin as a continuous variable and outcomes was also evaluated, as well as interaction by sex. Results: We included 574 patients (median = 76.5 years, IQR = 14, women 56.8%, increased troponin 34.1%) followed by a median of 3.8 years (IQR = 4.8). MACE occurred in 200 patients (34.8%). Increased troponin was independently associated with MACE (adjusted hazard ratio, 1.502, 95% CI, 1.130–1.998), ACS (adjusted hazard ratio, 2.488, 95% CI, 1.256–4.928), type I myocardial infarction (adjusted hazard ratio, 2.771, 95% CI, 1.212–6.333) and stroke (adjusted hazard ratio, 3.580, 95% CI, 1.888–6.787) but not with death, cardiovascular death or revascularization. Sensitivity analyses were consistent with these results. There was no interaction by sex. When assessed continuously, an increase in troponin concentrations was lineally associated with a steady increase in the risk of MACE. Conclusions: In patients with RAF who complain of chest pain, increased troponin levels are related to adverse cardiovascular outcomes.